Russian Orthodox Church and Covid-19 Pandemic: New Challenges and New Opportunities - Viktoriia Demydova (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
COVID-19 pandemic that reached Russia in March 2020, affected Russian Orthodox Church (ROC) in a negative way. Following the recommendations about the closure of the churches in Russia in late March 2020, ROC confronted serious challenges. This article problematizes position of ROC that faced a dilemma whether to close churches and put some of them onto the brink of poverty, or to perform religion’s main function and support citizens morally and spiritually. This article seeks to answer the question about the impact of COVID-19 pandemic on Russian Orthodox Church. It is argued that ROC has been affected by pandemic to a significant extent. First, ROC faced troubles in its relations with the government. Till the last minute, churchmen were resisting decision of the authorities to close the churches. Second, COVID-19 pandemic posed a threat to the position of ROC in Russian society: flock had distanced from the Church due to the isolation measures adopted. Third, financial contributions of the citizens have deteriorated that has led to the financial crisis within the Church. Fourth, split between different groups of clergy has deepen during the pandemic. Finally, pandemic caused not only new challenges, but also new opportunities for ROC. Thus, there is a chance to launch online services to avoid gap between flock and the Church. Second, the Church has the chance to redefine its ideology and worldview to address new issues of the post-COVID world. Author concentrates on the period between March 2020 and October 2021 and embraces qualitative methodology.